PENGARUH PENDIDIKAN KARAKTER KEAGAMAAN DAN OTORITAS ATASAN UNTUK BERBUAT CURANG TERHADAP PERILAKU TIDAK ETIS AKUNTAN - Sofyani, Hafiez; Rahma, Nadia (Jurnal Akuntansi dan Keuangan Indonesia, 2015)
The purpose of this study is to examine the influence of the religious character education, supervisor authority to cheat and the interaction of these factors toward unethical behavior of accountants in financial reporting. This study used experiment approach i.e. 2x2 factorial between subjects. These results reveal that when there is a superior authority to cheat, the subject will tend to cheat in making financial statements (unethical). Furthermore, subjects who received religious character education will tend to behave ethically in making financial reports. The results also indicate that the religious character education has ability to mitigate the urge to do unethical wich arise from authority of superiors to cheat factors.